Lactate dehydrogenase gene variability among predominant lactate utilizing ruminal bacteria - Fecskeová, L; Piknová, M; Javorský, P; Pristas, P (Folia microbiologica, 2010)
The inter- and intraspecies variability of lactate dehydrogenase (ldh) gene was determined among the predominant ruminal lactate utilizing bacteria. Nearly complete nucleotide sequences of ldh gene, encoding NAD-dependent lactate dehydrogenase of three Megasphaera elsdenii and six Selenomonas ruminantium strains, were obtained and compared. Phylogenetic analyses revealed a limited variability between the ldh sequences studied. The majority of differences observed were silent mutations at the 3rd position of codons. Surprisingly, the intraspecies diversity of the ldh gene among S. ruminantium isolates was higher than the interspecies level between S. ruminantium and M. elsdenii, which strongly suggests the possibility of acquisition of this gene by horizontal gene transfer.
Keywords: bodová mutace; Sequence Homology; Animals; molekulární sekvence - údaje; Lactic Acid; shluková analýza; L-Lactate Dehydrogenase; Cluster Analysis; bakteriální proteiny; DNA bakterií; DNA, Bacterial; Molecular Sequence Data; Sequence Analysis, DNA; genetická variace; Bacterial Proteins; Selenomonas; bachor; sekvenční homologie; Rumen; zvířata; fylogeneze; Megasphaera; sekvenční analýza DNA; Point Mutation; L-laktátdehydrogenasa; kyselina mléčná; Phylogeny; Genetic Variation